Analisis Faktor-Faktor yang Memengaruhi Konservatisme Akuntansi - Nurul Afyani Mumayiz; Cahyaningsih Cahyaningsih (Studi Akuntansi dan Keuangan Indonesia, 2020)
This study examines the effect of information asymmetry, litigation risk, investment opportunity set, and capital intensity on accounting conservatism. This study uses consumer goods sector companies listed on the Indonesia Stock Exchange from 2016 to 2018 as a research sample. The data analysis method used is panel data regression analysis using Eviews 9.0 software. The results showed that information asymmetry has a positive effect while litigation risk has a negative effect on accounting conservatism. Investment opportunity set and capital intensity have not to influence accounting conservatism. Suggestions for further researchers to examine prudence, in addition to accounting conservatism. For companies, investors, and creditors are expected to pay attention to the level